An optimized encryption algorithm and F function with dynamic substitution for creating S-box and P-box entries for blowfish algorithm - C, Rekha; G. N., Krishnamurthy (Institute of Advanced Engineering and Science, 2021)
In the field of cryptography, there has been a massive amount of enhancement in manipulating the plaintext which is unreadable, less prone to crackers and hackers, again manipulating this unreadable form to get back plaintext in some way. The Blowfish algorithm is a block cipher, has complex in structure in generating P-box and S-box entries using encryption algorithm. By simplifying the structure of encryption algorithm as well as F function with dynamic substitution, this can improve the performance by generating P-box and S-box entries of blowfish algorithm. In this paper, the proposed method simplifies the structure to produce P-box and S-box entries in order to reduce computational cost and demonstrates the performance of blowfish. The approach considers different security aspects namely EQ analysis, KS analysis, AV analysis, Entropy, Floating Frequency analysis and correlation of horizontally adjacent pixels in an encrypted image.